2014
DOI: 10.5194/tc-8-1989-2014
|View full text |Cite
|
Sign up to set email alerts
|

Topographic control of snowpack distribution in a small catchment in the central Spanish Pyrenees: intra- and inter-annual persistence

Abstract: Abstract. In this study we analyzed the relations between terrain characteristics and snow depth distribution in a small alpine catchment located in the central Spanish Pyrenees. Twelve field campaigns were conducted during 2012 and 2013, which were years characterized by very different climatic conditions. Snow depth was measured using a long range terrestrial laser scanner and analyses were performed at a spatial resolution of 5 m. Pearson's r correlation, multiple linear regressions (MLRs) and binary regres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
101
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(110 citation statements)
references
References 58 publications
6
101
2
1
Order By: Relevance
“…Hríbik et al, 2012) needs to be done in future studies. Revuelto et al (2014) concluded that topographic position index TPI helped explain variability of SD distribution. TPI at a 25 m searching distance was the best variable explaining snow depth distribution in their experimental catchment.…”
Section: Discussionmentioning
confidence: 99%
“…Hríbik et al, 2012) needs to be done in future studies. Revuelto et al (2014) concluded that topographic position index TPI helped explain variability of SD distribution. TPI at a 25 m searching distance was the best variable explaining snow depth distribution in their experimental catchment.…”
Section: Discussionmentioning
confidence: 99%
“…Ye et al (1998) and Kitaev et al (2005) showed that higher air temperatures caused an increase in snowfall in winter from 1936 through 1995, and thus greater snow depth was observed in northern Eurasia. Snow depth distribution and variation are controlled by terrain (i.e., elevation, slope, aspect, and roughness) and vegetation Grünewald et al, 2014;Revuelto et al, 2014;Rees et al, 2014;Dickerson-Lange et al, 2015). Snow depth is closely related to synoptic-scale atmospheric circulation indices such as the North Atlantic OscillationArctic Oscillation (NAO/AO).…”
Section: Introductionmentioning
confidence: 99%
“…The data set described here is novel in the Pyrenees because, for the first time, it represents high-spatialresolution information on the snowpack distribution and its evolution in time, as well as making continuous information available on meteorological variables. The high quality of the information obtained has already been exploited for different studies on the understanding of snowpack dynamics and the improvement of simulation approaches to snowpack evolution in mountain areas , 2014, Revuelto et al, 2014b, 2016a, 2016b. However, many scientific questions still go unanswered, such as the long-term influence of topography on snow dynamics, and the spatial distribution of snow during precipitation and strong wind events.…”
Section: Discussionmentioning
confidence: 99%
“…The data set consists of (i) continuous meteorological variables acquired from an automatic weather station (AWS), (ii) detailed information on snow depth distribution collected with a terrestrial laser scanner (TLS, lidar technology) for certain dates across the snow season (between two and six TLS surveys per snow season) and (iii) time-lapse images showing the snow-covered area (SCA) evolution. Some years of this data set have already been used to study the topographic control on snow depth distribution (Revuelto et al, 2014b), the spatial variability in snowpack at different distances or to investigate how detailed snowpack simulation could be improved by including snow distribution information (Revuelto et al, 2016a, b).…”
Section: Introductionmentioning
confidence: 99%